i dont really get it

cerenetie  Feb 21, 2018

1+0 Answers



a)  This is known as  the  Tangent-Secant Theorem....it says that :


"When a tangent and a secant are drawn from one single external point to a circle, the square of the length of tangent segment must be equal to the product of lengths of whole secant segment and the exterior portion of secant segment."


In plain English....it says that    TU^2  = TR* TS


b)  RT  =  9      ST  =  4


We can find  TU  thusly :


TU^2  = TR * TS


TU^2  = RT * ST


TU^2  =  (9) * (4)


TU^2   =  36       take the square root of both sides


TU  =   6




cool cool cool

CPhill  Feb 21, 2018

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details